Development of lightweight ferrocement sandwich panels for modular housing and industralized building system - Radin Sumadi, Salihuddin; Ramli, Mahyuddin (Faculty of Civil Engineering, 2008)

(untitled)
The development and construction of lightweight pre-fabricated sandwich structural elements in building construction is a growing trend in construction industry all over the world due to its high strength-to-weight ratio, reduced weight, and good thermal insulation characteristics. Sandwich construction element consists of thin face sheets or encasement of high performance material and a thick, lightweight and low strength material as core. Ferrocement is regarded as highly versatile thin material possessing superior properties which cannot be matched by other conventional thin materials. Aerated concrete is a cellular lightweight material which exhibits relatively higher strength than the conventional core materials such as foam. Additionally, sandwich construction deals with the problem of delamination of face sheets leading to their premature failure. This can be avoided by providing encasement over the core. This study was focused on the development of ferrocement encased aerated concrete sandwich wall elements, where ferrocement thin box encases a thick core of lightweight aerated concrete. The study was conducted in two phases. First phase involved the development of high workability and high performance slag-cement based mortar mix to cast proposed ferrocement encasement. The developed mortar was aimed to replace the traditional manual method of plastering the wire mesh by a mechanized casting method. The performance of mortar was investigated in terms of compressive strength, strength development, unit weight, effect of curing regime, and partial replacement of cement by weight with 50% and 60% of slag. The second phase of the study embarked on the development and investigation of the characteristics of ferrocement encased lightweight aerated concrete sandwich wall elements. To achieve the objective, about 600 specimens including large size wall elements were cast and tested. Ferrocement encasement was maintained at 12mm throughout the study. The parameters studied were compressive strength, flexural strength, failure mode, load-deflection behaviour, load-deformation behaviour, load-strain behaviour, unit weight, water absorption, initial surface absorption uniformity, and role of type and layers of the wire meshes. The results revealed the potential application of ferrocement encasement of lightweight aerated concrete to produce lightweight structural elements which leads towards the industrialization of building system. Finally, two mathematical models were developed to predict compressive strength of high workability slag-cement based mortars and the ultimate load of ferrocement encased aerated concrete sandwich wall elements. The values predicted from the mathematical models were 95%-100% accurate to the experimental results.